Optimisation of silicon content in Fe-Si alloys processed via Laser Powder Bed Fusion for an additively manufactured soft magnetic core - Gargalis, Leonidas (2021)
Additive Manufacturing (AM) of electric motors, specifically, Laser Powder Bed Fusion (LPBF), for rotating soft magnetic cores is of research interest because of its potential benefits in industry sectors such as energy, aerospace and automotive. AM, also commonly known as 3D printing (3DP), offers unrivalled design freedom and the capability to produce components with complex geometries from metal alloys that cannot be processed with conventional manufacturing methods (casting, injection moulding etc.). However, before AM becomes the norm in the production of novel electric drives and power generators, it is necessary to understand how the selection of materials in the motor affects the performance of the 3D printed active components (rotor, stator, windings). This thesis aims at enabling the AM of more compact, lightweight, reliable and efficient electric machines through the development of a comprehensive understanding of the metallurgy and material properties of the additively manufactured components of an electric drive. It focuses on two materials: a soft ferromagnetic alloy, namely silicon steel, for the soft magnetic core and high purity copper for the windings of the electric motor. The study investigated the mechanical, thermal and magnetic properties of high silicon steel (from Fe-3.5%wt Si up to Fe-6.9%wt Si) by adjusting – for the first time – the alloys’ chemistry in order to improve ductility and avoid the risk of in-process cracking; this is achieved by mixing pre-alloyed Fe-6.9%wt Si powder with high-purity Fe powder. Another material investigated, which has lately received increased interest both for electrical applications and heat exchangers, was pure copper. Although high purity copper is challenging to process with LPBF due to its high reflectivity, oxidation and high thermal conductivity, it was included in the study due the potential to further increase a motor’s performance by optimising the design of the windings in a 3DP electric motor. the materials under investigation were subjected to heat treatments. Annealing of the soft magnetic parts produced by LPBF changed their microstructure by increasing the grain size and increased their permeability. Experiments were also performed to investigate how the performance of a Switched Reluctance Motor (SRM) could be improved by manufacturing the soft magnetic rotor core using LPBF. A prototype SRM soft magnetic core was additively manufactured from 5%w.t. silicon steel and tested. We compared the efficiency of the motor with the 3D-printed rotor core to a motor with an identical but traditionally laminated rotor. This investigation has therefore, developed an understanding of the various aspects of the LPBF process for the successful manufacturing of a prototype functional electric motor. The results from this work can be used to advance the implementation of AM in the production of lightweight high-performance electrical machines and revolutionise the way electrical motors are designed and manufactured.